Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to teach myself complex analysis, and am reading about linear fractional transformations.

I want to find the transformation carrying the circle $|z|=2$ into $|z+1|=1$, $-2$ into the origin, and the origin into $i$.

My text states that the transformation is determined by prescribing a point $z_1$ on circle $C$ to correspond to a point $w_1$ on $C'$, and a point $z_2$ not on $C$ to correspond to $w_2$ not on $C'$. Then $z^\ast_2$ corresponds to $w^\ast_2$, the symmetric points of $z_2$ and $w_2$ in $C$ and $C'$, respectively. Then the transformation is obtained from the relation $(w,w_1,w_2,w^\ast_2)=(z,z_1,z_2,z^\ast_2)$ (those are cross-ratios).

I let $C$ be the circle $|z|=1$, and $C'$ be $|z+1|=1$. Then by the notions above $z_1=-2$, $w_1=0$, $z_2=0$, $w_2=i$. I calculate $z^\ast_2=\infty$ and $w^\ast_2=\frac{-1+i}{2}$.

So following what I've read, I have $(w,0,i,(-1+i)/2)=(z,-2,0,\infty)$. I don't understand how to gather the explicit form of the desired linear fractional transformation is from this, since $w$ and $z$ seem unknown to me. Could someone please explain what the transformation is now? Thank you.

share|improve this question

1 Answer 1

up vote 3 down vote accepted

Linear fractional transformations preserve cross-ratios, so if $w$ is an LFT we have $$(a,b,c,d)=(w(a),w(b),w(c),w(d)) \text{ for all }a,b,c,d\in\hat{\mathbb{C}}.$$

The utility of this is that if you know $w(b),w(c),w(d)$ for three known arguments $b,c,d$ as you do, then we can let $a$ be the independent variable $z$ and $w$ the dependent variable $w=w(z)$; solving for the variable $w$ in terms of $z$ will give us the desired transformation in the appropriate form,

$$w=\frac{\square\, z+\square}{\square\, z+\square}.$$

In particular, $(z,-2;0,\infty)=(w,0;i,\frac{-1+i}{2})$ says

$$\frac{(z-0)(-2-\infty)}{(-2-0)(z-\infty)} = \frac{(w-i)\left(0-\frac{-1+i}{2}\right)}{(0-i)\left(w-\frac{-1+i}{2}\right)}$$

$$-\frac{z}{2}=\frac{1+i}{2}\frac{w-i}{w-\frac{-1+i}{2}}.$$

Multiply by the righthand denominator, collect terms and solve for $w$ in a linear equation.

share|improve this answer
    
That's the crucial idea I was missing. Thank again anon. I find $$w=\frac{\frac{-1+i}{2}z+i-1}{z+1+i}.$$ –  Dedede Feb 10 '12 at 3:59

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.